Perceived Maternal Role Competence among the Mothers Attending Immunization Clinics of Dharan, Nepal - Shah Shrooti; Shrestha Mangala; Pokharel Nirmala; Shrestha Devkumari; Baral Dharanidhar (Shiraz University of Medical Sciences, 2016)
Background: Being a mother is considered by many women as their most important role in life. Women's perceptions of their abilities to manage the demands of parenting and the parenting skills they posses are reflected by perceived maternal role competence. The present study was carried out to assess the perceived maternal role competence and its associated factors among mothers. Methods: A descriptive cross-sectional research study was carried out on 290 mothers of infant in four immunization clinics of Dharan, Nepal. Data were collected using a standardized predesigned, pretested questionnaire (Parent sense of competence scale, Rosenberg's self esteem scale, Maternity social support scale). The data were analyzed using descriptive and inferential statistics and multiple regression analysis at 0.05 level of significance. Results: The mean score of the perceived maternal role competence obtained by mothers was 64.34±7.90 and those of knowledge/skill and valuing/comfort subscale were 31±6.01 and 33±3.75, respectively. There was a significant association between perceived maternal role competence and factors as the age of the mother (P<0.001), educational status (P=0.015), occupation (P=0.001) and readiness for pregnancy (P=0.022). The study findings revealed a positive correlation between perceived maternal role competence and age at marriage (r=0.132, P=0.024), per capita income (r=0.118, P=0.045), self esteem (r=0.379, P<0.001), social support (r=0.272, P<0.001), and number of support persons (r=0.119, P=0.043). The results of the step wise multiple regression analysis revealed that the major predictor of perceived maternal role competence was self esteem. Conclusion: The factors associated with perceived maternal role competence were age, education, occupation, per capita income, self esteem, social support, and the number of support persons.